Self-management Experience of Middle-aged and Older Adults With Type 2 Diabetes: A Qualitative Study - Fei-Ling Wu; Hsiu-Chen Tai; Jui-Chiung Sun (Elsevier, 2019)
Summary: Purpose: Diabetes mellitus has been either the fourth or fifth leading cause of death among Taiwanese adults during 1995-2015. Older adults with diabetes are at higher risk of developing diabetic macro-vascular and micro-vascular complications. The purpose of this study explored the self-management experiences of middle-aged and older adults with diabetes through a focus group. Methods: Purposive sampling was used to recruit patients with diabetes from the metabolic outpatient clinics of medical centers and regional hospitals in Taiwan. Two focus groups, comprising a total of 23 participants, were employed to collect data, and group discussions were held a total of four times in an education room that was distant from clinical areas. Results: Three themes were generated from analysis of the collected data: (1) "listening to the voice of the body and observing physical changes," (2) "re-recognizing diabetes and challenges," and (3) "self-management implementation dilemmas." This study provided new insights into the experiences of middle-aged and older adults in Taiwan regarding their self-management of diabetes. Conclusion: Healthcare teams should be involved in the self-management education of patients with diabetes as early as possible to reduce patients' anxiety and to develop more patient-centered, culture-sensitive clinical skills. In addition to monitoring patients' self-management, healthcare professor should pay more attention to patients' successful adaptation to and coexistence with the disease. Keywords: diabetes mellitus, focus groups, middle aged, self-management